1962
DOI: 10.1152/jappl.1962.17.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Loss of functional residual capacity in poliomyelitis

Abstract: Vital capacity, expiratory reserve volume, and functional residual capacity were determined on 11 normal controls and 25 postpoliomyelitis patients with a chronic flaccid respiratory paralysis. In general, the expiratory reserve volume diminished concomitantly with the vital capacity. As the residual volume was the same in the two groups the lost expiratory reserve volume of the patients had not been added to it. The expiratory reserve volume and functional residual capacity were significantly smaller in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
1

Year Published

1974
1974
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
3
1
Order By: Relevance
“…This is strong evidence that the fall in FRC in these patients is caused primarily by a decrease in the (outward) pull of the chest wall. This observation is consistent with other studies that demonstrated that the ability of the chest wall to recoil outwards decreased in normal volunteers when acute weakness of the respiratory muscles was produced by partial curarisation.12 Moreover, in our patients, a close relationship existed between the inspiratory muscle force and the decrease of both FRC and Pst (1) at FRC (fig 2), fu-rther suggesting that the reduction of the chest wall force is 'a, Analysis of lung volume restriction in patients with respiratory muscle weakness related to the degree of involvement of the inspiratory muscles. Such a decrease in the outward pull of the chest wall would contribute to the disproportionate loss of lung volume observed in our patients.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…This is strong evidence that the fall in FRC in these patients is caused primarily by a decrease in the (outward) pull of the chest wall. This observation is consistent with other studies that demonstrated that the ability of the chest wall to recoil outwards decreased in normal volunteers when acute weakness of the respiratory muscles was produced by partial curarisation.12 Moreover, in our patients, a close relationship existed between the inspiratory muscle force and the decrease of both FRC and Pst (1) at FRC (fig 2), fu-rther suggesting that the reduction of the chest wall force is 'a, Analysis of lung volume restriction in patients with respiratory muscle weakness related to the degree of involvement of the inspiratory muscles. Such a decrease in the outward pull of the chest wall would contribute to the disproportionate loss of lung volume observed in our patients.…”
supporting
confidence: 93%
“…Figure 8 illustrates the theoretical relationship between FRC and transpulmonary pressure at FRC when the PV characteristic of the chest wall remains unchanged (solid curve): when an increase in lung recoil pressure is the only cause of a decreased FRC, the Pst (1) at FRC must increase. By contrast, in most of our patients, the decrease in FRC was assoiciated with a decrease, not an increase, in Pst (1) at FRC (fig 8). This is strong evidence that the fall in FRC in these patients is caused primarily by a decrease in the (outward) pull of the chest wall.…”
contrasting
confidence: 68%
See 2 more Smart Citations
“…It is well established that weakness of the respiratory muscles causes a restrictive ventilatory defect with a reduction in TLC. However, the resting end expiratory position (FRC) in patients with respiratory muscle weakness can be decreased [19,[25][26][27], normal [28,29] or increased [30], while RV can be normal [19,27] or increased [22,[28][29][30]. To examine whether these differences could be due to differences in the distribution of respiratory muscle weakness, the current authors analysed values of FRC and RV in eight studies [2,19,22,[30][31][32][33][34] that have reported both lung volumes and inspiratory and/or expiratory muscle function.…”
Section: Significance Of the Findingsmentioning
confidence: 99%